The Problamatic of Non-Excestence of Legal Regulation of Electronic Contract in Kurdistan Region and its Solution - Hewa Ibrahim Qadir Al-Haidary; Jinan Mokaram Ahmed Barzanji (QALAAI ZANIST JOURNAL, 2022)
One of the most important problems facing electronic contracting in the Kurdistan Region is the absence of a special law regulating this type of contracts, despite the existence of a special law in Iraq, which is the Electronic Signature and Electronic Transactions Law No. (78) of 2012; Which led to the existence of a large legal gap in the region, which impeded the conclusion of the electronic contract in the region and destabilized it, and here a series of questions arise, including: Why is there not yet a law for electronic contracting in the Kurdistan Region? Why was the said law not implemented in the region? Does the Kurdish legislator not have an intention to enforce the mentioned law in the region? Or issuing a new legislation to regulate electronic contracting in the region? Therefore, the objectives of the research were to present the problem of the absence of such a legal regulation and how to address it, and we concluded that the best solutions to fill this legislative gap related to electronic contracting in the region is the issuing of a new modern law by the Kurdistan Parliament.